Home advantage in football in South-West Europe: Long-term trends, regional variation, and team differences - Pollard, R.; Gomez, M. A. (European Journal of Sport Science, 2009)
We examined the trends in home advantage in the professional football leagues of France, Italy, Spain, and Portugal since the start of each league more than 70 years ago. A total of 81,185 games were included, involving 244 different teams. Home advantage was quantified each season for each country as the number of points gained at home expressed as a percentage of all points gained at home and away. Home advantage was generally high in the early years of each league, especially in Spain and Italy (over 70%). There were then considerable fluctuations up to the late 1970s. During this time, home advantage was consistently highest in Spain, which could be explained by greater regional autonomy and more distinct local cultural identity. Since then there has been a major decline in all the countries, especially since the late 1990s. Each country has experienced its lowest ever level (60% or less) during the last four seasons. Possible explanations for this include the effects of changes that have taken place in the rules of football, such as greater use of substitutes and a series of new laws intended to discourage defensive play. In addition, free agency coupled with the rapid commercial development of football has weakened the relationship between players and their home city and fans. There were significant differences between teams within France, Italy, and Portugal (all P < 0.001) but not Spain (P = 0.145). Home advantage was higher for teams from the islands of Corsica and Sicily (P < 0 .001) and to a lesser extent Sardinia (P = 0.095). It was lower in teams that play in the four capital cities and also in Milan, whose two teams share the same stadium. This is consistent with the belief that the territorial feelings fostered in isolated, culturally distinct communities can lead to increased home advantage, while the reverse is the case in large cosmopolitan urban areas.